Pasantía en la empresa construcciones Majholica para la construcción de vivienda multifamiliar. - Pineda Silva, John Alejandro (Universidad Antonio Nariño, 2021)
Majholica constructions, is a company dedicated to the construction of civil works, execution of works and remodeling nationwide. The technical area is made up of engineers, technologists and technicians who have great knowledge in fields related to civil works that in turn offer security when executing the assigned works.